Potential of Bacillus subtilis Against SARS-CoV-2 – A Sustainable Drug Development Perspective - Khodavirdipour, Amir; Chamanrokh, Parastoo; Alikhani, Mohammad Yousef; Alikhani, Mohammad Sina (Frontiers in Microbiology, 2022)
The COVID-19 pandemic had anomalous yet inevitable impacts on the world’s economies, healthcare systems, and all other aspects of life. Researchers began to find the hidden roots to find a new horizon of hope, with the novelty of underrated resources. biosurfactants are sustainable biomolecules with an active surface, unique characteristics, and extensive uses. Bacillus species showed the highest biosurfactant activities and Bacillus subtilis is one of them. Antiviral, antimicrobial, and anti-inflammatory activity of B. subtilis proven recently. The great advantage is its non-toxic nature. Pro-inflammatory cytokines including IL-1 β, 6, 8, 12, 18, and TNF-α are secreted in higher amounts when neutrophils and monocytes are triggered by biosurfactant bacteria. This point of view furnishes the potential application of B. subtilis and its biomolecules against COVID-19, either in the form of a vaccine/therapeutic agent for a greener environment, healthier life, and environmental sustainability. Further in vivo and clinical trials are needed to validate this hypothesis.